Comparative Molecular Analysis Of P63 Gene Among Different Vertebrate Organisms - Wan Rosalina, Wan Rosli (Universiti Malaysia Sarawak, (UNIMAS), 2006)
In this study a region of p63. specifically regions of exon 7 to 8 is amplified using DNA extracted from various vertebrates to be used in restriction analysis, Information gathered from these analyses could aid in determining the molecular phylogenetics of the p63 gene to aid in the determination of appropriate model systems for future study in p63 form and function. A fragment corresponding to the exon 7 to 8 regions in humans have been successfully obtained and used for restriction analyses. A computational study on restriction site characterization of other vertebrates was carried out using sequences obtained from BLAST analysis.